Consequences of forgoing prescription drug subsidies among low‐income Medicare beneficiaries with diabetes. (27th April 2022) - Glynn, Alexandra; Hernandez, Inmaculada; Roberts, Eric T.
Abstract: Objective: The objective is to estimate the take‐up of the Medicare Part D Low‐Income Subsidy (LIS) among Medicare beneficiaries with diabetes and examine differences in out‐of‐pocket costs and prescription drug use between LIS enrollees and LIS‐eligible non‐enrollees. The LIS reduces out‐of‐pocket drug costs for low‐income beneficiaries; however, not all LIS‐eligible individuals are enrolled. Take‐up of the LIS, and consequences of forgoing this benefit among beneficiaries with diabetes, remains unknown. Data Sources: Health and Retirement Study linked to Medicare administrative data from 2008 to 2016. Study Design: We conducted two analyses among beneficiaries with diabetes. First, we estimated LIS take‐up stratified by income (≤100% of the Federal Poverty Level [FPL] and >100% to ≤150% of FPL). Second, to assess the consequences of forgoing the LIS among near‐poor beneficiaries (incomes >100% to ≤150% of FPL), we conducted propensity score‐weighted regression analyses to compare out‐of‐pocket costs, the prescription drug use, and cost‐related medication non‐adherence among LIS enrollees and LIS‐eligible non‐enrollees. Data Collection/Data Extraction: N/A. Principal Findings: Among Medicare beneficiaries with diabetes, 68.1% of those with incomes >100% to ≤150% of FPL received the LIS, while 90.3% with incomes ≤100% of FPL received the LIS. Among near‐poor beneficiaries, LIS‐eligible non‐enrollees incurred higher annual out‐of‐pocket drug spending (518; 95 [in USD]% CI: 370 [in USD], 667 [in USD]; p < 0.001), filled 7.3 fewer prescriptions for diabetes, hypertension, and hyperlipidemia drugs (95% CI: −11.1, −3.5; p < 0.001), and were 8.9 percentage points more likely to report skipping drugs due to cost (95% CI: 0.3, 18.0; p = 0.04), all compared to LIS enrollees. Conclusions: Despite providing substantial financial assistance with prescription drug costs, the LIS is under‐utilized among beneficiaries with chronic conditions requiring routine medication use. As policy makers discuss Part D reforms to address rising out‐of‐pocket drug costs, they should consider strategies to increase participation in existing programs that alleviate cost burdens among low‐income Medicare beneficiaries.